Nightmares without atonia as an early symptom of diffuse Lewy bodies disease - Paulo Roberto de Brito-Marques; Roberto Vieira de Mello; Luciano Montenegro (Arquivos de Neuro-Psiquiatria)
A male 70 years old patient with diffuse or ''pure'' Lewy body disease is described. The diagnosis was made based on clinical features of nightmares with no atonia, attention deficits with fluctuation in cognitive function, incapacity to find his way around the neighbourhood and other formerly familiar environments and mild neuropsychiatric symptoms. Neuropsychological assessment showed memory deficits, visuospatial and visuo-constructive disturbances. He had neither parkinsonism nor recurrent visual hallucinations typically well formed and detailled. Neuroimaging (computed tomography and magnetic resonance spectroscopy) showed mild diffuse cortical atrophy, mostly on the left temporal lobe and a decrease of N-acetil-aspartate levels. A cholinesterase inhibitor was prescribed to this patient during 6 months with clinically relevant behavioral effect. Diagnosis confirmation was made by post-mortem neuropathological findings. Macroscopical features were mild atrophy on the frontal, parietal and temporal lobes, notedly on the frontal lobes. Microscopically, there was neuronal loss and diffuse classic Lewy bodies. Brainstem (substantia nigra, raphe nucleus, locus coeruleus, pedunculopontine nucleus), limbic cortex, and neocortex (frontal, parietal and temporal) were the areas of predilection for Lewy bodies. Hematoxylin-eosin and Bielschowsky staining did not show neuronal swelling (balooned cell), argyrophilic inclusion (Pick's bodies), neurofibrillary tangles nor senile plaques. Immunohistochemical staining for anti-tau, anti-beta-amyloid, and anti-prion protein were negative. Antiubiquitine reaction was positive for Lewy body in the cerebral cortex and brainstem.